2010
DOI: 10.1021/jp1079586
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Si Atom Migration in the Framework of MSE-Type Zeolite YNU-2

Abstract: The change in distribution of Si atom defects in the framework of zeolite YNU-2 by steam treatment was investigated using powder X-ray diffraction and solid-state NMR spectroscopy. The precursor of zeolite YNU-2 (abbreviated to YNU-2P) with a three-dimensional pore system has a large number of Si atom defects (more than 10% of all T sites in a unit cell) around the supercage. These defect sites were confirmed by observation of a Q 3 ((-SiO) 3 Si-OH) resonance peak by 29 Si magic angle spinning NMR spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 28 publications
4
47
0
Order By: Relevance
“…41,42 For instance, the Q 4 -type Si atoms are related to Si(OSi) 4 . 43,44 The Q 3 -type Si atoms can be referred to Si(OAl)(OSi) 3 or terminal silanol groups in Si(OH)(OSi) 3 , 41,44 whereas the Q 2 -type Si atoms are referred to Si(OAl) 2 (OSi) 2 and geminal silanol groups in Si(OH) 2 (OSi) 2 . [44][45][46] From the results, it is clearly observed that at the initial stage of crystallization (2 h), the Q 4 peak (À111 ppm) is very broad and present as a shoulder peak of the Q 3 peak (À99 ppm), suggesting that the coordination environment of the corresponding framework Si atoms is distorted.…”
Section: Synthesis Of Hierarchical Zsm-12 Zeolite Nanosheetsmentioning
confidence: 99%
“…41,42 For instance, the Q 4 -type Si atoms are related to Si(OSi) 4 . 43,44 The Q 3 -type Si atoms can be referred to Si(OAl)(OSi) 3 or terminal silanol groups in Si(OH)(OSi) 3 , 41,44 whereas the Q 2 -type Si atoms are referred to Si(OAl) 2 (OSi) 2 and geminal silanol groups in Si(OH) 2 (OSi) 2 . [44][45][46] From the results, it is clearly observed that at the initial stage of crystallization (2 h), the Q 4 peak (À111 ppm) is very broad and present as a shoulder peak of the Q 3 peak (À99 ppm), suggesting that the coordination environment of the corresponding framework Si atoms is distorted.…”
Section: Synthesis Of Hierarchical Zsm-12 Zeolite Nanosheetsmentioning
confidence: 99%
“…Such migration of tetrahedral silicon species has recently been seen by Hong and co-workers in the zeolite natrolite 98 and for the healing of defects in zeolite YNU-2. 99 As a result, this process removes the vast majority of Ge atoms producing high Si/Ge ratios (greater than 200). Calcination of the material leads to IPC-2 zeolite that possesses the same connectivity as zeolite OKO.…”
Section: Self-organizationmentioning
confidence: 99%
“…Changes to the chemical composition of the product through the direct crystallization of a pure MSE phase is difficult to achieve, and tends to instead generate other phases such as BEA, MTW or MOR. We have previously succeeded in overcoming this limitation by utilizing the steam-assisted crystallization (SAC) method 19), 20) with some post-synthetic modification to obtain a pure-silica version of MSE (YNU-2) 4), 21) . This process requires a crystallization period of ca.…”
Section: Introductionmentioning
confidence: 99%